2013
DOI: 10.3851/imp2905
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Antiretroviral Therapy in South Africa: The Nuts and Bolts

Abstract: Public sector antiretroviral provision had a slow start in South Africa despite a raging epidemic and a World AIDS conference that shed significant public light on the disparities of therapy access globally. This was largely due to political prevarication in the midst of AIDS denialism. There has been an unprecedented expansion in the HIV treatment programme since 2008. As a result, South Africa now has the largest number of patients on antiretroviral drugs in the world, and South African life expectancy has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 74 publications
3
58
0
Order By: Relevance
“…[1,9,10] It focuses on the functioning of health systems [ 3,[11][12][13] and on the operational aspects of clinical care. [14][15][16][17][18][19] While the National Department of Health is committed to improving access to medicine, the procurement and distribution of medical supplies remains inadequate in many health districts. [20] Research on stock-outs has strived to quantify the extent and severity of shortages of medical supplies.…”
Section: In Practicementioning
confidence: 99%
“…[1,9,10] It focuses on the functioning of health systems [ 3,[11][12][13] and on the operational aspects of clinical care. [14][15][16][17][18][19] While the National Department of Health is committed to improving access to medicine, the procurement and distribution of medical supplies remains inadequate in many health districts. [20] Research on stock-outs has strived to quantify the extent and severity of shortages of medical supplies.…”
Section: In Practicementioning
confidence: 99%
“…2.2.3 Figure 3 shows the substantial increase in the number of patients receiving ART in South Africa from less than 50 000 in 2004 to almost 1.8 million in 2011, almost 2.5 million in 2013 (Bekker et al, 2014) and 3.1 million in 2014. 11 "A decision was made to increase the initiation threshold to 350 cells/μl for all adults, as well as to expand access thresholds for children" (Similela & Venter, 2014: 251 Bekker et al (2014);Mail and Guardian (2015) 12 were estimated to be living with HIV in South Africa, with an estimated 2.3 million on ART, and expanded access to 'third-line' drugs for patients experiencing resistance" (Similela & Venter, 2014: 261).…”
Section: 13mentioning
confidence: 99%
“…11 "A decision was made to increase the initiation threshold to 350 cells/μl for all adults, as well as to expand access thresholds for children" (Similela & Venter, 2014: 251 Bekker et al (2014);Mail and Guardian (2015) 12 were estimated to be living with HIV in South Africa, with an estimated 2.3 million on ART, and expanded access to 'third-line' drugs for patients experiencing resistance" (Similela & Venter, 2014: 261). During his 2014/2015 health budget vote speech, the Minister of Health announced that from January 2015, HIV-positive patients would be eligible for ART once their CD4 count fell below 500 cells/μl compared with the previous level of 350 cells/μl (Motsoaledi, 2014 13 Since then, life expectancy at birth has improved meaningfully with the help of the aggressive roll-out of ART.…”
Section: 13mentioning
confidence: 99%
“…Of those infected with HIV in SA, more than 50% are currently treated with antiretroviral therapy (ART), from a base of 7% in 2007. [8] A recent review of observational studies monitoring the risk of cancer concluded that the incidence of non-AIDS-defining cancers rose after starting ART, possibly owing to increased life expectancy or to the genomic instability caused by the drugs. [9] Two studies indicate that HIV-positive white individuals have a higher incidence of SCC than HIV-negative individuals.…”
Section: Researchmentioning
confidence: 99%